Magnetism of Stainless Steel 304 Due to Cold Rolling - Naila Mubarok; Hamdan Akbar Notonegoro (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2021)
304 austenitic stainless steel (SS 304) is widely used in the oil and gas industry for its resistance to high pitting and stress corrosion. However, Its ability to withstand wear resistance due to fine sand particles carried by oil and gas is very limited.  Cold rolling is one of the methods used to mechanically increase the hardness of SS 304 steel. As a result of this method there is a deformation of the structure which causes a phase transformation from austenite to martensite. This change is accompanied by the formation of magnetic properties in the new phase.The increase in the percentage of deformation is followed by an increase in the magnetic saturation value and a change in the magnetic coercivity. Magnetic saturation is influenced by the large population of martensite phase formed, while the magnetic coercivity is influenced by grain shape of the martensite phase. This magnetic property will respond to an external magnetic field. So that the identification of the deformation can simply be known by observing the interaction of the SS 304 material with a magnetic object that is brought near.